Question
Asked Nov 4, 2019

79.

fullscreen
check_circle

Expert Answer

Step 1

Plug g(x)=3x, then substitute x by 3x in f(x). 

Answer: (fog)(x)= sqrt(3x-1)

f(x) x-
g(x)=3x
(fog)(x)
=f(g(x))
=f (3x)
=V3x-1
help_outline

Image Transcriptionclose

f(x) x- g(x)=3x (fog)(x) =f(g(x)) =f (3x) =V3x-1

fullscreen
Step 2

Under square root we cna not have negative so 3x-1≥0

Answer: Domain of (fog)(x) is [1/3 , infinity)

Зx-120
3х21
3
Л
help_outline

Image Transcriptionclose

Зx-120 3х21 3 Л

fullscreen
Step 3

Replace x in g(x) by sqrt(x-1).

Answ...

(gof)(x)
=g(f (x)
g(x-1
3x-1
help_outline

Image Transcriptionclose

(gof)(x) =g(f (x) g(x-1 3x-1

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Other